International handbook of intelligence (Cambridge University Press, 2004)
This first international handbook of intelligence ever published provides a truly international perspective on the nature of intelligence. It covers intelligence theory, research, and practice from all over the globe. Areas include Great Britain, Australia, French-speaking countries, German-speaking countries, Spanish-speaking countries, India, Japan, Israel, Turkey, and China. The authors, internationally recognized experts in the field of intelligence, represent not just their own viewpoint, but rather, the full variety of viewpoints indigenous to the area about which they write. Each chapter deals with definitions and theories of intelligence, history of research, current research, assessment techniques, and comparison across geographical regions for the area under discussion. An intergrative final chapter synthesizes the diverse international viewpoints.